2014
DOI: 10.4081/ijas.2014.3308
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Slaughtering Age in Different Commercial Chicken Genotypes Reared According to the Organic System: 1. Welfare, Carcass and Meat Traits

Abstract: The carcass and meat quality of three different commercial chicken genotypes reared according to the organic system and slaughtered at two different ages (70 and 81 days) were compared. The used genotypes were Naked Neck (CN1), Kabir (KR4) and Ross 308 (R). All animals were raised in the facilities of a big Italian company, in production units of 3000 birds. Before slaughtering, plumage conditions, foot pad dermatitis as well as qualitative traits of carcasses, such as skin damage and the presence of breast bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
23
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 29 publications
7
23
0
6
Order By: Relevance
“…As expected from hybrid standards, the fast-growing Ross birds demonstrated higher daily weight gain than the slow-growing Rowan Ranger birds, resulting in higher body weight at slaughter and higher carcass weight. These results confirm previous findings on growth performance in fast-and slowgrowing hybrid birds (Castellini et al 2002;Fanatico et al 2005;Dal Bosco et al 2014). For the fast-growing hybrid Ross, the average growth rate was lower then what is described in the performance objectives in the ROSS manual (Aviagen 2014), possibly because of the lower protein quality in organic diets compared to the conventional diets used in the ROSS manual performance evaluation.…”
Section: Discussionsupporting
confidence: 88%
“…As expected from hybrid standards, the fast-growing Ross birds demonstrated higher daily weight gain than the slow-growing Rowan Ranger birds, resulting in higher body weight at slaughter and higher carcass weight. These results confirm previous findings on growth performance in fast-and slowgrowing hybrid birds (Castellini et al 2002;Fanatico et al 2005;Dal Bosco et al 2014). For the fast-growing hybrid Ross, the average growth rate was lower then what is described in the performance objectives in the ROSS manual (Aviagen 2014), possibly because of the lower protein quality in organic diets compared to the conventional diets used in the ROSS manual performance evaluation.…”
Section: Discussionsupporting
confidence: 88%
“…However, Somsen et al cantly different *P < 0.05, **P < 0.01 (2004) reported that the average yield of chicken giblets was 4.36% at an average live weight prior to slaughtering of 1898 g in the case of conventional broilers. Dal Bosco et al (2014) affirmed rapid muscular-skeletal development in fast-growing birds as well as excessive development of the cardiovascular system in slow-growing chickens; in line with these observations, OC showed higher heart percentages than CC. The gizzards of OC were heavier and yielded more due to differences in feeding (access to grassy paddock) which could include various kinds of forage, insects, worms and sand particles.…”
Section: Discussionsupporting
confidence: 74%
“…On the basis of our previous studies (Castellini et al 2002a(Castellini et al , 2002bDal Bosco et al 2014a, 2014b and commercial information, the genotypes were sub-categorised with regard to their growth rate: slow (GR < 24 g/d; A, L, CL), medium (25 < GR 40 g/d; G, RM, K, NN) or fast-growing (GR > 41 g/d; R).…”
Section: Birds Diets and Slaughteringmentioning
confidence: 99%